The Ottoman Conquest of Rhodes - González Castrillo, Ricardo (Anaquel de Estudios Árabes, 2007)
The aim of this article is to comment and analyse an unpublished manuscript from the Royal Library of Madrid. This original document briefly talks about some of the battles which have taken place between the Hospitaller Knights of St. John of Jerusalem and the Ottomans during the last siege of Rodes. In fact, the manuscript is an anonymous letter, written in characters from the 16th century. The singularity of this manuscript resides in its dating the siege at 1520 and claiming that it was carried out by Sultan Selim I.